2014
DOI: 10.1371/journal.pone.0092222
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma DPP4 Activity Is an Independent Predictor of the Onset of Metabolic Syndrome in Chinese over 4 Years: Result from the China National Diabetes and Metabolic Disorders Study

Abstract: AimsTo determine whether fasting plasma Dipeptidyl Peptidase 4 (DPP4) activity and active Glucagon-Like Peptide-1 (GLP-1) were predictive of the onset of metabolic syndrome.MethodsA prospective cohort study was conducted of 2042 adults (863 men and 1,179 women) aged 18-70 years without metabolic syndrome examined in 2007(baseline) and 2011(follow-up). Baseline plasma DPP4 activity was determined as the rate of cleavage of 7-amino-4- methylcoumarin (AMC) from the synthetic substrate H-glycyl-prolyl-AMC and acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…Following the data interpretation in the light of indexes of kidney function, DPP4 serum activity remained independently associated with lower insulin sensitivity. In support to our study results, Yang et al (2014) [28] have recently demonstrated that DPP4 activity is significantly higher in healthy subjects with higher blood pressure and insulin resistance determinated by HOMA-IR index in apparently healthy Chinese man and woman. Recent experimental and clinical studies suggest that DPP4 inhibition reduces blood pressure [29] although the underlying mechanism remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
“…Following the data interpretation in the light of indexes of kidney function, DPP4 serum activity remained independently associated with lower insulin sensitivity. In support to our study results, Yang et al (2014) [28] have recently demonstrated that DPP4 activity is significantly higher in healthy subjects with higher blood pressure and insulin resistance determinated by HOMA-IR index in apparently healthy Chinese man and woman. Recent experimental and clinical studies suggest that DPP4 inhibition reduces blood pressure [29] although the underlying mechanism remains poorly understood.…”
Section: Discussionsupporting
confidence: 92%
“…Subjects were instructed to maintain their usual physical activity and diet for at least three days before undergoing an oral glucose tolerance test (OGTT). After an overnight fast of ≥10 h, venous blood samples were collected to measure HbA1c, fasting plasma glucose (FPG), fasting insulin, blood lipids Plasma glucose levels, insulin, TC, TG, HDL-C, LDL-C, IL-6, hs-CRP, M6P-R, nitrotyrosine, and 8-iso-PGF2a and c-IMT were measured as previously described [5,6,9,20]. B-mode ultrasonography of the common carotid artery (CCA) was performed using an ultrasound machine (Toshiba; Toshiba Medical Systems, Tokyo, Japan).Each subject was examined in the supine position, with the head elevated ≤45° and a side tilt of 30° to the right and then the same to the left.…”
Section: Measurementsmentioning
confidence: 99%
“…Recent studies have demonstrated that DPP4 is also a newly identified adipokine that has been shown to contribute to hyperglycemia, insulin resistance, dislipidemia, oxidative stress and inflammation [4][5][6][7][8][9][10], all which have been suggested to be involved in the pathogenesis of subclinical atherosclerosis [11,12]. More importantly, a recent in vitro study proved that soluble DPP4 directly activated the MAPK and NF-κB signaling cascade involving PAR2 and resulting in the induction of inflammation and proliferation of human vascular smooth muscle cells (hVSMC), all direct effects of sDPP4 on signaling, proliferation and inflammation could completely be prevented by DPP4 inhibition [13].…”
Section: Introductionmentioning
confidence: 99%
“…20 The human IGF-2R enzyme-linked immunosorbent assay (ELISA) kit (Ever Systems Biology Laboratory Inc., Los Angeles, CA, USA) and human IL-6 ELISA Kit (R&D Systems, Minneapolis, MN, USA) were used in this study to determine serum IGF-II/M6P-R and IL-6 according to the manufacturer's protocols. Hs-CRP was measured by immunoturbidimetric assay (Roche Diagnostics, Indianapolis, IN, USA).…”
Section: Biochemical Analysesmentioning
confidence: 99%